INVENTARISASI SERANGGA HAMA PADA KOPRA DI KECAMATAN TOBELO KABUPATEN HALMAHERA UTARA - CATHERINE.E. GABRIEL; J. MANUEKE; E. R.M. MERAY; T. OGIE (COCOS, 2020)
ABSTRACTThis study aims to determine the pest insects that attack copra commodities and determine thepopulation density of each type or species of pest insects that attack copra in Tobelo District,North Halmahera Regency. The research method used was a survey method. The survey wasconducted at a copra warehouse in Rawajaya Village, Gosoma Village, and Wosia VillageTobelo District, North Halmahera Regency. Sampling uses the method "Purposive Sampling"which is deliberate sampling at copra warehouses that have been attacked by pests. Observationswere carried out 5 times with one week observation time intervals. The results of the studyfound six types of pest insects in copra commodities in Tobelo District, North HalmaheraRegency, namely Necrobia rufipes De Geer, Carpophilus dimidiatus F, Tribolium castaneumHbst, Dermestes sp., Sitophylus sp. and Ephestia cautela walk. The highest average populationdensity of pest insects is N. rufipes, population density is 116.57 tails per 500 gr copra, followedby C. dimidiatus, population densities 16.67 tails per 500 gr copra, T. castaneum, populationdensity 14.53 tails per 500 gr copra, Dermestes sp., densely populated 4.57 tails per 500 grcopra), E. cautella, population densities 0.33 tails per 500 gr copra and Sitophilus sp., populationdensities 0.06 tails per 500 gr copra.Keywords : Inventory, Pest Insect, Copra